The Constant And Variable In Arabic Structure Of Verbal Sentence - Ali Salama Abdel Halim Abu Sharif (Ijaz Arabi Journal of Arabic Learning, 2023)
The “verbal sentence” in linguistic structures and texts is characterized by possessing a set of constant and variable (changeable) phenomena. The present research aims to investigate all the phenomena that occur in the “verbal sentence” and classify them in terms of “constant” and “variable,” as there are numerous beliefs, differences, and confusion in this regard. The research problem addresses the constant and variable phenomena in forming “verbal sentences.” “Al-Isnad” (attribution) between the two parts of a “verbal sentence” emergence or deletion of any of the two parts of the sentence, rules of “verb” in the sentence regarding masculine or feminine. Dual or plural rules of “subject” with the “accusative object” in rank are the most significant. In dealing with these phenomena, the researcher adopted the descriptive analytical approach based on describing the phenomenon, analyzing it, and drawing a conclusion. The researcher found constant phenomena when composing “verbal sentences,” and variable phenomena occur in the composition structure related to the producer or the recipient. The research recommends that the phenomenon of constant and variable should be applied to all linguistic forms, such as nominal sentences and transcribers. Linguistic methods like “nominal sentence” and its “nawasikh,” like an exclamation, praising or criticizing someone, and preference.